Near-infrared-spectroscopy derived vs lactate thresholds in elite nordic skiers - Forot, J.; Schorderet, F.; Burdet, C.; Brocherie, F.; Millet, G. P. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Cross-country skiing and biathlon are endurance sports that require an accurate exercise intensity prescription to optimize performance. Traditional methods for monitoring exercise intensities (e.g., lactate or heart rate) have limitations in terms of comfort and precision during on-field training. Recently, near-infrared spectroscopy (NIRS) has emerged as a new method for non-invasive monitoring of muscle oxygenation. The Moxy Monitor, a portable NIRS device, was shown to enable accurate determination of thresholds, when compared to lactate thresholds [1]. However, to date, the optimal location of the sensor remains unknown, particularly in sports as Nordic ski using both upper- and lower limbs. Therefore, this study aimed to evaluate the feasibility and accuracy of using NIRS to determine breakpoints (i.e. BP1 and BP2) compared to first (LT1) and second (LT2) lactate thresholds and to compare different muscle sites in male and female elite cross-country skiers and biathletes.